2020
DOI: 10.1177/1943387520948709
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Aesthetic and Functional Outcome Following Structural Fat Grafting for Facial Scars and Contour Deformity

Abstract: Study Design: This is a prospective observational study of 60 consecutive cases with facial scars and contour deformity who underwent structural fat grafting. Objectives: The aim of the present article is to highlight how fat grafting helps to improve aesthetic and functional outcome in facial scars and contour deformities. It also highlights the factors that need to be considered while planning autologous fat grafting to get better aesthetic results. Methods: This is a prospective observational study of 60 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The aesthetic outcome as scored on the VAS scale showed a mean score of 8.2, and 6 patients (20%) scored the aesthetic outcome with a VAS score of 10. Such a mean score was superior to that obtained by Rao et al (16) who reported an aesthetic outcome with a mean VAS score of 7.1 (±1.26) using fat grafting to improve aesthetic and functional outcomes in facial scars.…”
Section: Discussioncontrasting
confidence: 75%
“…The aesthetic outcome as scored on the VAS scale showed a mean score of 8.2, and 6 patients (20%) scored the aesthetic outcome with a VAS score of 10. Such a mean score was superior to that obtained by Rao et al (16) who reported an aesthetic outcome with a mean VAS score of 7.1 (±1.26) using fat grafting to improve aesthetic and functional outcomes in facial scars.…”
Section: Discussioncontrasting
confidence: 75%
“…Autologous fat grafting (ie, lipotransfer) of adipose tissue‐derived stem cells (ADSCs) for patients with keloids has been shown to improve scar texture, pliability volume, and elasticity. This is achieved by the inhibition of fibroblast proliferation and ECM formation 54 …”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Contour deformities of the face requiring soft tissue augmentation are usually associated with hyperpigmentation of overlying skin (A. Bashir et al, 2020). These deformities often result from a variety of conditions like trauma, infections, and certain acquired diseases (Rao et al, 2020). Contour deformities of the face cause both functional as well as esthetic problems for the patients (Nigmatov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bashir et al, 2020). These deformities often result from a variety of conditions like trauma, infections, and certain acquired diseases (Rao et al, 2020). Contour deformities of the face cause both functional as well as esthetic problems for the patients (Nigmatov et al, 2021).…”
mentioning
confidence: 99%